Peripartum energy metabolism of prolific ewes and their progeny in response to prepartum feeding and litter size - M. Plante-Dubé; R. Bourassa; P. Luimes; S. Buczinski; F. Castonguay; R. Gervais (Animal)
In late gestation, the increased energy demand to support the rapid fetal growth can induce an acute negative energy balance associated with a high risk of pregnancy toxemia, especially for prolific ewes (carrying two or more fetuses). The current study was conducted to evaluate the effects of dietary energy during the last 6 weeks prepartum on the energy metabolism dynamic responses and the newborn lamb metabolic profile in prolific ewes. Forty-five crossbred (Dorset × Romanov) ewes were randomly assigned to 1 of 3 dietary energy densities: ECTRL: 8.36 MJ of metabolizable energy (ME)/kg DM for weeks −6 to −3 relative to lambing, followed by 10.01 MJ ME/kg DM for weeks −2 and −1; EINCR: weekly increments from 7.99 to 12.69 MJ ME/kg DM; and EHIGH: 10.87 MJ ME/kg DM for the last 6 weeks of gestation. Dry matter intake (DMI; daily) and energy intake (MEI; daily), blood concentrations of beta-hydroxybutyrate (BHB) and glucose (every other day), as well as plasma concentrations of non-esterified fatty acids (NEFAs; weekly), BW and body condition score (BCS; twice weekly) were determined throughout the experimental period. The effect of time on DMI and MEI varied based on dietary energy densities and litter size. During the last week before lambing, DMI decreased for EHIGH and EINCR ewes, as well as for ewes carrying quadruplets. On average, during week −5 to week −2 of gestation, EHIGH promoted the highest DMI and MEI, resulting in an increase of 0.16 BCS points between the pretreatment week and week −1 prepartum. In contrast, during the same period, BCS of ECTRL and EINCR ewes decreased by 0.35 and 0.19 points, respectively, which was reflected by higher NEFA concentrations compared with EHIGH ewes. The greater litter size was also associated with decreased BCS. Compared with twin-bearing ewes, for which BCS remained stable, BCS decreased for triplet-, and even more intensively for quadruplet-bearing ewes. Consequently, plasma NEFA concentrations were higher for quadruplet-bearing ewes than for twin− and triplet-bearing ewes, especially during the last week prepartum. Blood BHB concentrations increased from 0.63 to 1.13 mM over time. Regardless of dietary treatments, in the last week prepartum, blood BHB concentrations increased for quadruplet-bearing ewes, being 2.6 and 2.2 times greater than for twin− and triplet-bearing ewes, respectively. These results suggest that dynamic responses of energy metabolism in late gestation of prolific ewes are influenced by both dietary energy level and litter size.